Development and Validation of an Android-based Trail Making Test Application (TMT App) for Cognitive Evaluation in Healthy and Depressed Individuals - Rohit Verma; Ishita Dhyani (Indian Journal of Psychological Medicine)
Background: The Trail Making Test (TMT) is a famous neuropsychological test that is frequently used. The structure of a paper-and-pencil-based TMT is highly likely to be adapted to a mobile app. The current study aimed to develop and validate an Android-based tablet version of TMT. Methods: The application (TMT App) was developed using an Android-based platform. Healthy and depressed individuals ( n = 133) were assessed on both the TMT versions (paper-based version and app-based version) in a random cross-over design. The device’s usability was ascertained using the system usability scale (SUS) in a subset of individuals ( n = 65). Results: There was a significant positive correlation between the individual processing times for the paper-based TMT-A and the app-based TMT-A in both healthy and depression groups [r(63) = 0.55, p < .001; and r(66) = 0.77, p < .001, respectively]. The individual processing times of the paper-based TMT-B and the app-based TMT-B also showed a significant positive correlation in both healthy control and depression groups [r(63) = 0.67, p < .001; and r(66) = 0.89, p < .001, respectively]. There was a positive correlation of age with TMT-A and TMT-B for either version. Both groups had similar positive responses to the usability of the TMT App. Conclusion: The preliminary validation results for the TMT App suggest that it is significantly correlated with existing paper-and-pencil methods, and that it is user friendly.